Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to find the following sum:

$$ \sum\limits_{k=0}^\infty (-1)^k \frac{(\ln{4})^k}{k!} $$

I decided to substitute $x = \ln{4}$:

$$ \sum\limits_{k=0}^\infty (-1)^k \frac{x^k}{k!} $$

The first thing I noticed is that this looks an awful lot like the series expansion of $e^x$:

$$ e^x = \sum\limits_{k=0}^\infty \frac{x^k}{k!} $$

The only obstacle is the $(-1)^k$ term. I tried getting rid of it by rewriting:

\begin{align*} \sum\limits_{k=0}^\infty (-1)^k \frac{x^k}{k!} &= 1 - x + \frac{x^2}{2!} - \frac{x^3}{3!} + \frac{x^4}{4!} - \frac{x^5}{5!} + \dots\\ &= (1 + \frac{x^2}{2!} + \frac{x^4}{4!} + \dots) - (x + \frac{x^3}{3!} + \frac{x^5}{5!} + \dots)\\ &= \sum\limits_{k=0}^\infty \frac{x^{2k}}{(2k)!} - \sum\limits_{k=0}^\infty \frac{x^{2k+1}}{(2k+1)!} \end{align*}

These sums look a lot like the series expansions of $\sin(x)$ and $\cos(x)$:

\begin{align*} \sin(x) &= \sum\limits_{k=0}^\infty (-1)^k \frac{x^{2k+1}}{(2k+1)!}\\ \cos(x) &= \sum\limits_{k=0}^\infty (-1)^k \frac{x^{2k}}{(2k)!} \end{align*}

However, these sums do have a $(-1)^k$ term, just when I got rid of it! So now I'm stuck. Can someone help me in the right direction?

share|cite|improve this question

2 Answers 2

up vote 5 down vote accepted

Note that $$e^{-x}=\sum_{k=0}^\infty \frac{(-x)^k}{k!}=\sum_{k=0}^\infty (-1)^k\frac{x^k}{k!}$$

share|cite|improve this answer

You started fine, but then you got sidetracked:

$$\sum\limits_{k\ge 0}(-1)^k \frac{(\ln{4})^k}{k!}=\sum_{k\ge 0}\frac{(-\ln 4)^k}{k!}=e^{-\ln 4}=\frac1{e^{\ln 4}}=\frac14\;.$$

share|cite|improve this answer
21:51:06 vs 21:51:14. Hmmmm... – Pedro Tamaroff May 24 '13 at 21:52
Please give a more subtle answer for a question with the homework tag the next time: my goal was not to get the right answer (I don't need this site for that), but to understand how to solve such problems. I am still grateful for your help and thus upvoted your answer, but I will accept Peter Tamaroff's answer, for he gave me what I asked for: a hint to help me in the right direction. – Tim Vermeulen May 24 '13 at 22:00
@timjver: (I tend to give hints, but in this case I consider the difference between the two answers pretty negligible.) In future if you want only a hint, you should probably say so explicitly: the homework does not necessarily mean that only a hint is appropriate (or wanted), and phrases like help me in the right direction are also used by people who want any amount of help, up to and including a full solution. Given that I’ve seen full solutions offered even when the explicit request was made, you might even want to put it in boldface. – Brian M. Scott May 24 '13 at 22:07
Right, I'll keep that in mind for future questions. :) Thank you. – Tim Vermeulen May 24 '13 at 22:09
@timjver: You’re welcome. (I just wish that I’d realized that you really did just want a hint; it’s always a pleasure to see that kind of request.) – Brian M. Scott May 24 '13 at 22:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.